KEEFEKTIFAN PERANGKAT RENCANA PELAKSANAAN PEMBELAJARAN MELALUI PENELITIAN BERBASIS PERANCANGAN - Noorlatifah Noorlatifah; Suryajaya Suryajaya; Muhammad Zaini (Journal of Banua Science Education, 2021)
Teachers still have difficulty practicing critical thinking skills so that learning outcomes and critical thinking skills in science learning are less than optimal. This study aims to evaluate the effectiveness of the quality of the lesson plans developed using a guided inquiry learning model with the topic of change in form at SMPN 22 Banjarmasin. The method used is development research. The device development model used is the Tessmer model, which includes the stages of self-evaluation, expert review, one to one, small group, and field test. The lesson plans developed were syllabus, lesson plans, teaching materials, LKPD, and assessment test. The subjects in the study were students of class VII SMPN 22 Banjarmasin. The results showed that the lesson plan using the guided inquiry model, the topic of change in form was classified as effective, including the learning outcomes of students with a completeness percentage of 76% and had reached the KKM set by the school. Students 'critical thinking skills are categorized as very good, students' psychomotor skills use very good categorized filter papers, characterized behavior includes disciplinary aspects that are very well categorized and aspects of responsibility are very good. Social skills include aspects of working together which are categorized as quite good, aspects of donating ideas are categorized as very good, and spiritual attitudes of gratitude are categorized as very good. Based on the following research results, it can be concluded that the lesson plan tools through design-based research are effective.Keywords: effectiveness, lesson plans tools, guided inquiry, learning outcomes, critical thinking skillsAbstrakGuru masih mengalami kesulitan dalam melatihkan kemampuan berpikir kritis sehingga hasil belajar dan keterampilan berpikir kritis dalam pembelajaran IPA kurang optimal. Penelitian ini bertujuan mengevaluasi keefektifan kualitas perangkat RPP hasil pengembangan menggunakan model pembelajaran inkuiri terbimbing topik perubahan wujud di SMPN 22 Banjarmasin. Metode yang digunakan adalah penelitian pengembangan. Model pengembangan perangkat yang digunakan adalah model Tessmer, meliputi tahap self evaluation, expert review, one to one, small group, dan field test. Perangkat RPP yang dikembangkan adalah silabus, RPP, bahan ajar, LKPD, dan lembar penilaian. Subyek dalam penelitian adalah peserta didik kelas VII SMPN 22 Banjarmasin. Hasil penelitian menunjukkan bahwa perangkat RPP menggunakan model inkuiri terbimbing topik perubahan wujud tergolong efektif meliputi hasil belajar peserta didik dengan persentase ketuntasan sebesar 76% dan telah mencapai KKM yang ditetapkan sekolah. Keterampilan berpikir kritis peserta didik terkategori sangat baik, keterampilan psikomotor peserta didik menggunakan kertas saring terkategori sangat baik, perilaku berkarakter meliputi aspek disiplin terkategori sangat baik dan aspek tanggung jawab terkategori sangat baik. Keterampilan sosial meliputi aspek bekerja sama terkategori cukup baik, aspek menyumbangkan ide terkategori sangat baik, dan sikap spiritual rasa syukur terkategori sangat baik. Berdasarkan hasil penelitian berikut dapat disimpulkan bahwa perangkat RPP melalui penelitian berbasis perancangan efektif.Kata kunci: keefektifan, perangkat RPP, inkuiri terbimbing, hasil belajar, keterampilan berpikir kritis